Nanotherapies based on bacterial metabolism: Mechanisms, design and application - Jiaping Chen; Yanli Zhang; Xin Luo; Yuting Zeng; Ping Xiao; Xian Ding; Sijie Qiu; Qianlin Li; Qianwen Deng; Simin Wang; Ruofei Lin; Xiuwen Chen; et al. (Materials Today Bio)
Bacterial metabolism provides the essential materials and energy for growth and reproduction. Through complex transformations and electron transfer, bacteria convert external nutrients into useable forms and achieve pathogenicity in the human body. In recent years, with the global spread of antibiotic resistance, traditional antibiotic treatments have become increasingly ineffective and may even exacerbate the imbalance of the human microbiota. As a novel type of antibacterial agent, nanomaterials possess superior characteristics when compared with traditional antibiotics. The most significant feature is their capacity to target multiple stages of bacterial metabolism, which endows them with substantial potential in the realm of antibacterial therapy. In the early stages of nutrient entry into bacterial metabolism, nanomaterials can not only induce oxidative stress imbalance and interrupt the transformation of metabolic substances, but also hinder the energy production process by disrupting the cell membrane or interfering with the operation of the electron transport chain. Moreover, through rational and meticulous design in terms of size, surface properties, solubility, and catalytic effects, nanomaterials can exhibit even more considerable antimicrobial potential. Therefore, this article, starting from the perspective of bacterial metabolism, provides a detailed discussion on the antimicrobial mechanisms, application background, and challenges and opportunities faced by nanomaterials, with the aim of guiding future research and promoting the further development of nanomaterials in the field of antimicrobial therapy.